Morning Journal Activities With a Montessori Approach to Stimulate Integrative Holistic Development in Early Childhood - Ahmad Nur Bachtiar Febriyanto; Naila Fikrina Afrih Lia (FKIP - Universitas Riau, 2026)
Morning journaling is a Montessori-based learning activity that plays a crucial role in preparing young children. This approach emphasizes child-centered learning, freedom to choose activities, and the use of concrete media consistent with early childhood learning principles. This study aims to describe the implementation of Montessori-based morning journaling in stimulating the holistic and integrative development of early childhood inMona School IT Kindergarten. The research method used is a qualitative method with data collection analysis techniques in the form of observation, interviews, and documentation. This study shows that the morning journal activity based on the Montessori approach is able to stimulate the holistic integrative development of early childhood. The Montessori method emphasizes a learning method that provides freedom. This freedom means that children can choose their own activities and are free to play. Thus, the study shows that the implementation of the morning journal approach based on the Montessori method at Mona School IT Kindergarten is effective in helping stimulate the holistic integrative development of children, and also forming independent character in early childhood has been done well.